2020
DOI: 10.1111/sms.13843
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative side effects of androgen abuse. The HAARLEM study: A one‐year prospective cohort study in 100 men

Abstract: An estimated 4-6% of fitness center visitors uses anabolic-androgenic steroids (AAS). Reliable data about adverse reactions of AAS are scarce. The HAARLEM study aimed to provide insight into the positive and negative effects of AAS use. One hundred men (≥18 years) who intended to start an AAS cycle on short notice were included for follow-up. Clinic visits took place before (T 0), at the end (T 1), and three months after the end of the AAS cycle (T 2), and one year after the start of the cycle (T 3), and compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…Thus, the great attention for physical attractiveness and muscularity could lead to body dissatisfaction and low self-esteem [42] and could prompt the abuse of anabolic steroids in MSM [49,50]. It is largely demonstrated that some of the latter (e.g., androgens) may interfere with sexual behavior [51], especially after their discontinuation [52].…”
Section: Importance Of Body Imagementioning
confidence: 99%
“…Thus, the great attention for physical attractiveness and muscularity could lead to body dissatisfaction and low self-esteem [42] and could prompt the abuse of anabolic steroids in MSM [49,50]. It is largely demonstrated that some of the latter (e.g., androgens) may interfere with sexual behavior [51], especially after their discontinuation [52].…”
Section: Importance Of Body Imagementioning
confidence: 99%
“…Despite benefits such as increased muscle growth, improved body image, and enhanced sports performance (Evans 2004;Sagoe et al 2014a;Smit et al 2020a), human case studies, surveys, and experimental studies suggest that AAS induce a plethora of physical and psychological adverse side effects. Cardiovascular disorders, particularly cardiomyopathy, are major physical side effects of AAS use (Baggish et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Details on the side effects reported by subjects of the HAARLEM study are published separately ( 18 ) but none reported dyspnoea or peripheral oedema at the end of the cycle (T 1 ). Two of 31 subjects complained of fatigue.…”
Section: Resultsmentioning
confidence: 99%